Market orientation and new-to-the-world products: Exploring the moderating effects of innovativeness, competitive strength, and environmental forces - Augusto, Mário (2008)
Recently, there has been a keen research interest in exploring the relationship between market orientation and new product development. The empirical results, however, are mixed, and this means that we do not fully understand these linkages. Furthermore, research concerning the antecedents of new-to-the-world products has focused on the study of a single product. However, it is of obvious interest for organizations to understand what drives a firm's overall performance in the exercise of developing very innovative products. In this empirical study, the authors take a component-wise approach to investigate the effects of market orientation in new-to-the-world product innovation, and examine how other variables interplay with market orientation to affect product development. Firstly, the findings show that both customer and competitor orientations, together with interfunctional coordination, are important drivers of a firm's new-to-the-world product innovation. Secondly, the results indicate that the components of market orientation are differentially moderated by a firm's innovativeness, competitive strength, and also by environmental forces.